Structural Engineering of Zinc‐Blend/Wurtzite BN Superlattices. Issue 48 (21st December 2018) - Ming, Bangming; Wang, Changhao; Guo, Gencai; Xu, Lichun; Wang, Ruzhi; Yan, Hui
Abstract: By constructing Zinc‐Blende (ZB)/Wurtzite (WZ) boron nitride (BN) (ZB1‐x /WZx ‐BN) superlattices (SLs), their electronic structure and mechanical properties were investigated by first‐principles techniques based on density functional theory. It is found that the band structure is significantly modulated by the ratio of WZ phase in ZB/WZ‐BN SLs. With the increase of WZ ratio, the band gap of SLs decreases and then increases dramatically. More importantly, transformation from type‐I to type‐II band alignment between ZB and WZ can be tuned by adjusting the ratio of WZ to be >0.6. In addition, a universal expression of the band gap is proposed to reveal a nonlinear dependence of the band gap within the structure of SLs as induced by from the interface effect achieved via structural transformation. The elastic constants results revealed that the change of ZB/WZ ratio poses no significant effect on the mechanical properties. The effect of structure modulation on band structure and mechanical properties is significantly important for future engineering of novel semiconductor SLs. Abstract : The electronic structures of ZB1‐x/WZx‐BN on homojunction interface were systematically investigated with first‐principles calculations. A nonlinear dependence of band gap on the composition of SLs is obtained through the introduction of a higher‐order term expressed as cx 3 (1‐x) to perfectly describe the interface effect.